Performance Assessment of CPU Scheduling Algorithms: AScenario-Based Approach with FCFS, RR, and SJF - P.Kavitha (The Bioscan, 2024)
This study presents an extensive examination of CPU scheduling algorithms, focusing on the First-Come, First-Served (FCFS), Round-Robin(RR), and Shortest-Job-First (SJF) strategies through a carefully designed scenario-based approach. By deploying a Java-based simulation to dynamically generate random process arrival and burst times, this study simulates a variety of operational conditions to test these scheduling algorithms’ adaptability and performance in environments that closely resemble real-world computing scenarios. The research aims to explore the effects of dynamic quantum size allocation on RR scheduling and assess its impact on system performance metrics such as response time and context switching overhead. Through a detailed analysis, this study seeks to providenew insights into the operational efficiency of the FCFS, RR, and SJF scheduling strategies, highlighting their strengths, limitations, and applicability across different computing environments.